POLA PENGASUHAN DAN PEMENUHAN HAK DASAR ANAK BURUH MIGRAN PEREMPUAN - Selvy Anggriani Syarif (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2018)
Parents, community, and goverment have a responsibility to make sure child’s right are respected, protected, and fulfilled. This needs to be supported with a good parenting. This paper aims to: analyse parenting of child of women migrant workers in Soppeng district and describe fulfillment of child’s right of women migrant workers in Soppeng district. This study was used qualitative and quantitative approach. A total 44 families of women migrant workers was used data in this study. Quantitative data was analyzed descriptively, and qualitative data was analyzed with 3 different plots (reduction, presentation, and make conclusion) at the same time. There are some factors that affect the parenting of child of women migrant workers, specifically parent’s education, family economic condition, sex of the child, number of children, children’s age, and the availability of a dependable caregiver. The result showed that women migrant workers families are divided into 3 stages in the family life cycle and there are 7 parenting patterns in the family of women migrant workers. Many families involve mother’s family than father’s family. However, not all parenting patterns can fulfill child’s rights. All stakeholders should be involved to upgrade the fulfillment of child’s right and improve their life.